Optimization of Maintenance and Use of Gensets in the Armed Forces - Hederić, Željko; Barešić, Dejan; Barukčić, Marinko (International Journal of Electrical and Computer Engineering Systems, 2014)
The Armed Forces use a great number of various types of gensets. The aim is to reduce this large number of diverse genset types, that is, to standardize the equipment used with the aim of simplifying maintenance and modes of use. For this reason, tests are conducted which should provide factual conclusions as to the types of gensets which are both most favourable for use and maintenance and also meet the conditions required by international military operations. One of these requirements is the possibility of using the kerosene fuel F-34 for diesel engines. It is well known that diesel engines running on kerosene fuel develop less power, which can result in the direct reduction of generator rotation speed at rated loads. Therefore, we conducted tests on one type of electric genset by using resistor load. The additional goal was to conduct tests on other types of electric motors by using different types of loads. It was particularly important to conduct the tests during the acceleration of an asynchronous motor since gensets are also used in technical workshops to run compressor units and in these instances asynchronous motors often turn on. So, in order to facilitate conductivity, we also developed mathematical models and computer simulations.